2017
DOI: 10.1002/hbm.23622
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of imprecision inPETMRIrigid registration to imprecision in amyloidPETSUVRmeasurements

Abstract: Quantitative measurement of β‐amyloid from amyloid PET scans typically relies on localizing target and reference regions by image registration to MRI. In this work, we present a series of simulations where 50 small random perturbations of starting location and orientation were applied to each subject's PET scan, and rigid registration using spm_coreg was performed between each perturbed PET scan and its corresponding MRI. We then measured variation in the output PET‐MRI registrations and how this variation aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…Therefore, it is reasonable that MRI was more correctly registered to amyloid negative images than to amyloid positive images. Schwarz et al [12] indicated that Alzheimer's disease had a larger registration error than the control group in amyloid PET images, and our results are consistent with their report.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is reasonable that MRI was more correctly registered to amyloid negative images than to amyloid positive images. Schwarz et al [12] indicated that Alzheimer's disease had a larger registration error than the control group in amyloid PET images, and our results are consistent with their report.…”
Section: Discussionsupporting
confidence: 93%
“…It is important to understand the registration accuracy in order to use the software appropriately because PET images change a lot depending on not only the choice of tracers but also disease progression in dementia PET. One study about registration accuracy of amyloid PET and MRI using SPM has been reported by Schwarz CG, Jones DT, Gunter JL, Lowe VJ, Vemuri P, Senjem ML, et al [12]. They analyzed the registration accuracy for some groups classified by clinical disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we used a reference region previously shown to provide the most stable reference over time: the average of both the whole cerebellum and the cerebral white matter. 31 A partial volume correction with the method of Muller-Gartner et al 32 was tested but was found to add error, particularly due to limitations in coregistering PET to MRI, 33 and therefore the data presented are not partial volume corrected.…”
Section: Methodsmentioning
confidence: 99%
“…The benefit of WM over the cerebellum as a reference region is that there is a larger region over which to average the signal, potentially leading to less noise. WM measurements may also be more resistant to small degrees of misregistration during image quantification (12). In addition, the cerebellar signal is collected at the edge of the scanner field of view where sensitivity is lower (8,9).…”
mentioning
confidence: 99%